Iron Deficiency Anemia - Rodrigo, Luis (IntechOpen, 2019)
Iron deficiency (ID) and iron deficiency anemia (IDA) are prevalent conditions all over the world. The groups at highest risk are children, pre-menopausal women and socially disadvantaged people. Diagnose of ID using a full blood examination and iron studies can be difficulted by concomitant inflammation. Management of ID involves identification and treatment of its cause, as well as effective iron replacement. Patients who fail to respond to iron replacement will performed an endoscopy to exclude internal bleeding. Both enteral and parenteral iron are effective at replacing iron. For adult patients, we recommend trialling daily oral iron (30-100 mg of iron) as the first-line therapy. Patients who fail to respond to oral iron replacement can be safely managed with intravenous iron.